Comparable regional hypertrophy of the knee extensor muscles in response to resistance training with machines versus free weights: a randomized within-subject approach. - Amanuma, Magellan T.; Ikeda, Pedro Luiz T.; Sakamoto, Mariana T.; Justino, Julio Cesar; Abreu, Nicollas Silva; de Sena Silva, Maria Vitória; de Salles Painelli, Vitor (Journal of Bodywork & Movement Therapies, 2025)
Muscle hypertrophy response to resistance training (RT) with machines and free weights is widely debated in the literature. Understanding which form of exercise is superior for muscle hypertrophy has therapeutic and ergogenic repercussions. Therefore, we compared muscle hypertrophy response between RT performed with free weights (FW) vs. machines (MACH). Randomized within-subject design. Eight young, healthy, untrained women (age: 22 ± 5 years; 62.0 ± 8.7 kg; 1.71 ± 0.05 m; BMI: 21.4 ± 3.3 kg m2) had each of their legs submitted to RT with FW or MACH. RT included exercises targeting the knee extensor muscles (FW: lunge; MACH: inclined leg press), 3 days·week−1, for 9 weeks. Muscle hypertrophy was determined pre- and post-RT through ultrasound to assess MT of the vastus lateralis (VL) and rectus femoris (RF) at their proximal (50 %) and distal (70 %) portions. The Mixed Model was conducted for data analysis, with significance set at p ≤ 0.05. No between-group differences were identified for any of the muscles and portions before RT (all comparisons, p > 0.05). MT increases were detected for both FW and MACH in RF50 % (respectively, +10.7 %, p = 0.027; and +8.9 %, p = 0.051), RF70 % (respectively, +24.8 %, p = 0.019; and +27.3 %, p = 0.017), VL50 % (respectively, +13.3 %, p = 0.011; and +12.1 %, p = 0.031) and VL70 % (respectively, +12.7 %, p = 0.046; and +15.7 %, p = 0.016), indicating that RT-induced muscle hypertrophy occurred across all muscles and portions. However, Group × Time interaction was not identified for RF50 % (p = 0.816), RF70 % (p = 0.588), VL50 % (p = 0.679) or VL70 % (p = 0.635) MT values. FW and MACH were comparably effective to induce muscle hypertrophy in previously untrained women.